Chronic Care for Attention-Deficit/Hyperactivity Disorder: Clinical Management from Childhood Through Adolescence. (February 2020) - Moss, Cierra M.; Metzger, Kristina B.; Carey, Meghan E.; Blum, Nathan J.; Curry, Allison E.; Power, Thomas J.
ABSTRACT: Objective: Impairments generally persist when children diagnosed with attention-deficit/hyperactivity disorder (ADHD) mature into adolescence. To examine changes in ADHD care during the transition from childhood to adolescence, we conducted a retrospective, longitudinal cohort study of patients diagnosed with ADHD before the age of 10 years to assess changes from preadolescence through adolescence in (1) frequency by which primary care providers offer ADHD care to patients, (2) range of concerns assessed during patient encounters, and (3) treatments implemented or recommended. Methods: We identified patients from 3 practices included in a large primary care network who (1) were born between 1996 and 1997, (2) were diagnosed with ADHD before the age of 10 years, and (3) received primary care continuously from age 9 through late adolescence. Clinical care was compared among patients in preadolescence (age 9–11), early adolescence (age 12–14), and late adolescence (age 15–18). Results: Children diagnosed with ADHD before the age of 10 years were less likely to have a documented visit for ADHD during late adolescence (41% of patients) compared with preadolescence (63%, p < 0.001). Evidence of monitoring for depression, suicide, and substance abuse increased from preadolescence to adolescence ( p < 0.001) and occurred in about 90% of adolescent patients. However, monitoring for risky sexual activity occurred in only about 50% of adolescents. Discussions of medication diversion and driver readiness were essentially not documented. Conclusion: The findings raise concerns about how primary care providers manage adolescents with a history of ADHD. Improving monitoring of risky sexual behavior and driver readiness and providing patient education about medication diversion are needed.